Budaya Berpikir Positif sebagai Modal Utama Harmoni Sosial dan Integrasi Bangsa - Sulaiman Mamar (Antropologi Indonesia, 2014)
This article analyzes the positive thinking culture of each ethnic group in Poso, CentralSulawesi. This article also examines the factors that cause degradation of ethnic culture ofpositive thinking so as to serve as guidelines for public behavior. The study was conductedby observation, in-depth interviews, and analysis of qualitative data. The research foundthe degradation of cultural values with several contributing factors. Finally, the model canbe described cultural transformation of positive thinking is right to apply to the youngergeneration. The transformational models of positive thinking culture are: parents need tocomprehend positive thinking culture and teach it to their children; the need to teach morals,positive thinking culture and the regional language in schools; an emphasis of parents andleaders as role-leader for the younger generation; the empowerment of traditional leadersin socializing positive thinking culture; the need for emerge individual to direct their thoughtand actions to positive matter.Keywords: positive thinking culture, cultural transformation, social harmony and nationalintegration